Facile synthesis of the fungus-derived natural products: N, N′-dipalmitoleyl urea (C16:1) and N, N′-dioleyl urea (C18:1). Issue 8 (18th April 2022) - Stec, Jozef; Pecic, Stevan
Abstract: Oxalyl chloride is one of the most versatile reagents used in organic synthesis. Oxalyl chloride was employed in the convenient one-pot, two-step synthesis of the fungus-derived naturally occurring lipoids: N, N' -dipalmitoleyl urea (C16:1 ) and N, N' -dioleyl urea (C18:1 ). The two symmetrical diacyl urea-based natural products were previously identified as fungus-specific pathogen-associated molecules (PAMs), which act as inflammatory mediators during fungal infection. The highly lipophilic natural lipoids were efficiently synthesized from commercially available reagents in yields ranging from good to very good. Graphical Abstract: